1990
DOI: 10.1016/0378-1097(90)90405-f
|View full text |Cite
|
Sign up to set email alerts
|

Colonial variation and fimbriation of Actinobacillus actinomycetemcomitans

Abstract: Three colonial variants of Actinobacillus actinomycetemcomitans, which formed transparent rough (TR)-, transparent smooth (TS)-, and opaque smooth (OS)-surfaced colonies, were described in relation to their fimbriation. TR- and TS-cells were adhesive to agar and glass surfaces but not the OS-cells. The examination by electron microscopy revealed that TR-cells were highly fimbriated but not TS- and OS-cells. Thus, TS-cells seemed to be an intermediate type. The fimbriae were isolated from TR-cells by suspending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 11 publications
3
106
0
1
Order By: Relevance
“…P. Smith, T. Ruiz and K. P. Mintz related to the expression of fimbriae (Inouye et al, 1990). Visualization of individual cells by transmission electron microscopy revealed fimbriae associated with the clinical strain (VT1257, Fig.…”
Section: Colony Morphology Of Transformed Parent and Morc Mutant Strainsmentioning
confidence: 97%
See 1 more Smart Citation
“…P. Smith, T. Ruiz and K. P. Mintz related to the expression of fimbriae (Inouye et al, 1990). Visualization of individual cells by transmission electron microscopy revealed fimbriae associated with the clinical strain (VT1257, Fig.…”
Section: Colony Morphology Of Transformed Parent and Morc Mutant Strainsmentioning
confidence: 97%
“…This conversion typically arises from point mutations in the promoter region of the tad locus, which includes the fimbrial transport machinery (Wang et al, 2005). Loss of fimbriae is accompanied by an increase in colony size and loss of the star-shaped colony morphology characteristic of fimbriated strains of A. actinomycetemcomitans (Inouye et al, 1990). Afimbriated strains also display reduced surface adherence and do not colonize host tissues as effectively as the fimbriated form (Schreiner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fimbriae have been recognized as one of the colony morphology determinants often associated with freshly isolated rough colonies. Rough A. actinomycetemcomitans strains isolated from periodontitis patients produce colonies with a star-shaped interior structure and possess abundant fimbriae (Inouye et al, 1990;Fine et al, 1999). Rough colonies can convert to a smooth phenotype upon in vitro subculture, and this conversion is accompanied by loss of fimbriae and some adhesiveness (Inouye et al, 1990;Fine et al, 1999).…”
Section: Fimbriaementioning
confidence: 99%
“…Fap, a fimbrial subunit, has been isolated, cloned, and sequenced. This fimbrial subunit is expressed predominantly in fimbriated strains (Inouye et al, 1990). Genetic analysis revealed that this fimbrial gene is next to a gene locus coding for the rough colony-specific proteins, RcpA and RcpB (Haase et al, 1999 (Chen and Wilson,199.…”
Section: Fimbriaementioning
confidence: 99%
“…Clinical isolates autoaggregate and secrete long, bundled pili (Flp fibrils) (Holt et al, 1980;Scannapieco et al, 1987;Rosan et al, 1988;Inoue et al, 1998;Kachlany et al, 2001b;Henderson et al, 2003;Fine et al, 2006). In vitro A. actinomycetemcomitans can produce rare, stable, nonadherent, and nonaggregative genetic variants that form smooth, large colonies and fail to produce Flp fibrils (Wyss, 1989;Inouye et al, 1990;Fine et al, 1999Fine et al, , 2006Kachlany et al, 2000Kachlany et al, , 2001aHenderson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%